2020
DOI: 10.31234/osf.io/wsg89
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulatory Focus and Perceived Safety with Casual Partners: Implications for Perceived Risk and Casual Sex Intentions During the COVID-19 Pandemic

Abstract: Background: Fundamental motives for survival help people regulate their goal pursuit, by shaping perceptions, feelings and actions. Motives for security (i.e., prevention focus) are associated with risk awareness and risk avoidance, whereas motives for pleasure (i.e., promotion focus) are associated with risk taking. Purpose: During the COVID-19 pandemic, survival needs and health risks are particularly salient. Hence, people focused on prevention (vs. promotion) should be more aware of health risks, more care… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 55 publications
8
24
0
Order By: Relevance
“…Although single people increase their risk of COVID-19 infection by having sex with casual partners, recent research has shown that single people are using condoms less frequently since the pandemic Dacosta et al, 2021). Yet, another study has shown that single people with a prevention (vs. promotion) focus reported stronger intentions to use condoms with casual partners (Rodrigues & Kärgel, 2020). However, this research did not establish if people's motives translate into sexual activity during the pandemic.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…Although single people increase their risk of COVID-19 infection by having sex with casual partners, recent research has shown that single people are using condoms less frequently since the pandemic Dacosta et al, 2021). Yet, another study has shown that single people with a prevention (vs. promotion) focus reported stronger intentions to use condoms with casual partners (Rodrigues & Kärgel, 2020). However, this research did not establish if people's motives translate into sexual activity during the pandemic.…”
mentioning
confidence: 68%
“…According to Regulatory Focus Theory (Higgins, 1998(Higgins, , 2015, people with a prevention (vs. promotion) focus tend to be more averse to risks and perceive more threats to their health (e.g., Lemarié et al, 2019;Rodrigues et al, 2019;Zou & Scholer, 2016) and are more likely to engage in health protection behaviors (e.g., Fuglestad et al, 2013;Rodrigues, Lopes, Pereira, et al, 2020;Zou & Scholer, 2016). For single people, this extends to stronger intentions to protect their sexual health (Rodrigues et al, 2019;Rodrigues & Kärgel, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations